2016
DOI: 10.1016/j.egypro.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recycled Polyurethane Polyol on the Properties of Flexible Polyurethane Foams

Abstract: Flexible PU foam was synthesized by using recycled PU foam polyol (Infrigreen) which contain 4 functionality obtained from glycolysis wasted PU foam, as a polyol. PU foam is prepared by incorporation of recycled PU foam polyol 2, 4, 6, 8 and 10wt% in petrochemical polyol (CARADOL.SA34-05) which contain 2 functionality. Triethlylenediamine (TEGOAMIN 33) was used as the gelling catalyst. Polyether modified polysiloxane (TPGAOSTAB B8715 LF2) was the surfactant. Distilled water was used as a blowing agent to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…As reported by other authors, 40 it can be observed in Figure 3 that an increase in the recovered polyol content causes an improvement in the tensile properties of the PU foams probably due to the higher crosslinking and higher urea formation. In fact, it can be observed that the foams synthesized with glycolyzates obtained employing DEG as cleavage agent show the highest values of tensile strength since these recovered polyols present the highest proportion of compounds that increase the crosslinking and the urea domains in the PU structure (glycolysis agent excess and byproducts).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…As reported by other authors, 40 it can be observed in Figure 3 that an increase in the recovered polyol content causes an improvement in the tensile properties of the PU foams probably due to the higher crosslinking and higher urea formation. In fact, it can be observed that the foams synthesized with glycolyzates obtained employing DEG as cleavage agent show the highest values of tensile strength since these recovered polyols present the highest proportion of compounds that increase the crosslinking and the urea domains in the PU structure (glycolysis agent excess and byproducts).…”
Section: Resultssupporting
confidence: 81%
“…In a general way, it can be observed that the foams preserve the polyhedral cell structure independently on the content of recovered 40 In fact, the higher the viscosity of the polyol mixture, the more restricted the CO 2 to be expanded, giving as a result a decreasing in the PU foam cell size. 40,45 Figure 6 shows the cell-size distribution of all synthesized foams.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…CO 2 takes a large volume of the cell structure of PU foam as a result of the reaction of polyether polyol and isocyanate. CO 2 has a thermal conductivity coefficient of 0.0137 W (m −1 ·K −1 ), which is bottom than that of air 0.0233 W (m −1 ·K −1 ) . As a result, the LPET/FPU sandwich composites have a greater thermal retention property.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the sound absorption characteristic of PU foams can be controlled by varying raw materials such as polyol, isocyanate, crosslinking agent, blowing agent, surfactant, catalysts, and any other additives. 29 The properties of PU can be developed by changing the ratio of these raw materials. The acoustic properties of materials include sound absorption and sound insulation.…”
Section: Introductionmentioning
confidence: 99%